Developing Application in Anticipating DDoS Attacks on Server Computer Machines - Anthony Anggrawan; Raisul Azhar; Bambang Krismono Triwijoyo; Mayadi Mayadi (Universitas Bumigora, 2021)
The use of server computer machines in companies is primarily a web hosting server that is very easy to experience threats, especially external security threats such as attempts to infiltrate, hacking, viruses, and other malicious attacks. Having a secure server is indispensable for working online and especially if involved in business-related network transactions. The Server's realization to be safe from threats is to protect the server machine's security on the hardware and software side and pay attention to network security that goes to the server machine. Generally, firewall applications on router devices have configuration limitations in securing the network, namely non-integrated applications. In other words, it is necessary to manage the perfect firewall configuration to anticipate Distributed Daniel attacks of Service (DDoS) attacks. Therefore, this study aims to integrate existing firewall applications for router devices into an integrated program to secure the network. The methodology used is the Network Development Life Cycle (NDLC). The research results on this developed application program can overcome DDoS attacks without setting up a firewall on the router device and can automatically monitor DDoS attack activities from outside the Server. Securing servers from DDoS attacks without setting up a firewall on the router device and automating the monitoring of DDoS attack activity from outside the Server are the novelties of this study that have not been available in previous studies.